Use of Evidence-Centered Design to Develop Learning Maps-Based Assessments. Issue 2 (3rd April 2019) - Bechard, Sue; Clark, Amy; Swinburne Romine, Russell; Karvonen, Meagan; Kingston, Neal; Erickson, Karen
Abstract : Evidence-based approaches to assessment design, development, and administration provide a strong foundation for an assessment's validity argument but can be time consuming, resource intensive, and complex to implement. This article describes an evidence-based approach used for one assessment that addresses these challenges. Evidence-centered design principles were applied to create a task template to support test development for a new, instructionally embedded, large-scale alternate assessment system used for accountability purposes in 18 US states. Example evidence from the validity argument is presented to evaluate the effectiveness of the template as an evidence-based method for test development. Lessons learned, including strengths and challenges, are shared to inform test-development efforts for other programs.